The Cine Club de Lima - Bedoya, Ricardo (2009)
Cine Club de Lima was the most important cinematography culture spreading institution of the fifties. It was also the precursor of other movie clubs of following decades, which would bring together important Peruvian intellectuals from every art form, who would together promote cultural entertainment. This piece describes ”Cine Club Lima” origins and dissolution, while taking into account its programs.